Diversidade genética em coleções amazônicas de germoplasma de cupuaçuzeiro [Theobroma grandiflorum (Willd. ex Spreng.) Schum.] - Alves, Rafael Moysés; Silva, Carlos Rogério De Sousa; Silva, Maria Suellem Da Conceição [UNESP]; Silva, Darly Caroline De Souza; Sebbenn, Alexandre Magno (Sociedade Brasileira de Fruticultura, 2013)
This study aimed to evaluate the genetic diversity and relatedness of 24 accessions of Theobroma grandiflorum, originating from three units of Embrapa, aiming their use as parents in hybridization specie programs. The genetic markers used were heterologous microsatellite loci developed for cocoa. In the population studied 45 alleles were found. The effective average number of alleles per locus (2.33) was less than the average number of alleles per locus (3.21), indicating that many alleles have low frequency. The observed heterozygosity at polymorphic loci ranged from 0.33 to 1.00 with a mean of 0.54 and expected heterozygosity ranged from 0.48 to 0.76 with a mean of 0.54. The fixation index medium between loci (0.003) was not significantly different from zero. The estimate of relatedness between pairs of individuals indicates that some may be relatives, including half-brothers and clones. The results suggest that the accesses of T. grandiflorum analyzed contain a moderate level of genetic diversity and absence of inbreeding and therefore great potential for use in breeding programs.

Este trabalho teve por finalidade avaliar a diversidade genética e o parentesco de 24 acessos de Theobroma grandiflorum, introduzidos de três unidades da Embrapa, objetivando sua utilização como genitores no programa de hibridação da espécie. Os marcadores genéticos utilizados foram lócus heterólogos de microssatélites desenvolvidos para cacaueiro. Foram encontrados 45 alelos na população estudada. O número médio efetivo de alelos por lócus (2,33) foi menor do que o número médio de alelos por lócus (3,21), indicando que muitos alelos têm baixa frequência. A heterozigosidade observada nos lócus polimórficos variou de 0,33 a 1,00 com média de 0,54 e a heterozigosidade esperada variou entre 0,48 a 0,76 com média de 0,54. O índice de fixação médio entre lócus (0,003) não foi significativamente diferente de zero. A estimativa do parentesco entre pares de indivíduos indica que alguns podem ser parentes, entre meios-irmãos e clones. Os resultados sugerem que os acessos de Theobroma grandiflorum analisados contêm um moderado nível de diversidade genética e ausência de endogamia e, portanto, grande potencial para utilização em programas de melhoramento genético.
Genetic diversity in brasilian amazon collections of cupuassu tree germplasm [Theobroma grandiflorum (Willd. ex Spreng.) Schum]
Keywords: Microssatélite; endogamia; diversidade genética; Microsatellite; inbreeding; genetic diversity